Postoperative dissemination of fat particles in the subarachnoid pathways. - McAllister, J D; Scotti, L N; Bookwalter, J W (American Journal of Neuroradiology, 1992)
A case of postoperative dissemination of fat particles into the cerebrospinal fluid pathways is reported. Following removal of a foramen magnum meningioma, a postoperative MR scan showed fat droplets in the basal cisterns and in the frontal horns of the lateral ventricles. The patient was asymptomatic and a repeat MR scan 7 months later was normal, with resolution and clearing of the previously noted cerebrospinal fluid fat.